The impact of negative emotional reactions on parental vaccine hesitancy after the 2018 vaccine event in China: A cross-sectional survey - Ruyu Sun; Xiaomin Wang; Leesa Lin; Ning Zhang; Lu Li; Xudong Zhou (Taylor & Francis Group, 2021)
Vaccination programs are cost-effective for preventing communicable diseases, yet vaccine events caused vaccine crises among parents nationwide, which has created challenges for current and future vaccination programs. This study aimed to investigate parents' emotional reactions (i.e., anger and anxiety) toward the 2018 vaccine event in China and explore the associations between parental emotional reactions and vaccine decision-making. A cross-sectional survey was conducted among 1,135 parents in 2018. Five-point Likert scales were provided for respondents to rank their anger and anxiety toward the event, and their vaccine-related trust and intentions before and after the event. Multiple logistic regression analyses were employed to explore the associations. Regarding the vaccine event, 576 (50.8%) and 402 (35.4%) respondents felt very angry and angry, and 310 (27.4%) and 516 (45.5%) respondents felt very anxious and anxious, respectively. Altogether, 797 (70.3%) respondents reported a lower trust in domestically produced vaccines after the event, and 704 (62.3%) respondents reported declines in intention to choose domestically produced vaccines for their children. Multiple logistic regression analyses revealed that anxiety was a predictor of lower trust and intention after the event (p < .001), anger was a predictor of lower trust (p = .005), and both were risk factors for declines in trust and intention (p < .01). This study confirmed that negative emotional reactions toward a vaccine event were important contributors for parental vaccine decisions. Health authorities and facilities are encouraged to act in a timely manner to reduce the public's negative emotions by providing rapid crisis responses.